A fast block partitioning algorithm for VVC intra coding based on depthwise separable convolution - Zhen YE; Guoxiang WANG; Junfeng SONG; Haokun LIU; Tiansong LI (Dianxin kexue)
The joint video exploration team (JVET) proposed versatile video coding (VVC) as a new video coding standard, and its quadtree plus multi-type tree (QTMTT) partition structure brings effective coding performance improvements.However, it brings about a sharp increase in encoding complexity, which greatly increases the encoding time.In order to solve the above problems, a fast block partitioning algorithm for VVC intra coding based on depthwise separable convolution was proposed.The pixel of coding unit (CU) was used as input, and the texture information feature of CU was extracted through depth-separable convolution.Therefore, accurate partition mode prediction was realized in the QTMT structure in VVC, and the complexity of the encoder was reduced by skipping low-probability partition modes.Experimental results show that the proposed algorithm saves 18% to 48% of encoding time on the VTM 15.2, and only brings an average performance loss of 0.15%.And the additional complexity brought by the lightweight depthwise separable convolution calculation is also negligible.